Adult Distal Radius Fracture Management. Issue 22 (15th November 2021) - Chhabra, A. Bobby; Yildirim, Baris
Abstract : Distal radius fractures (DRFs) are some of the most commonly encountered fractures, and the incidence is increasing. Optimal treatment remains controversial. Critical evaluation of the initial imaging is necessary to recognize fracture characteristics and stability. The fracture pattern, injury mechanism, soft-tissue injury, patient characteristics, and surgeon preference are generally taken into consideration when choosing the most appropriate modality. Volar plating has become the workhorse of surgical DRF management but is not without complications. The surgeon should be comfortable using a wide variety of techniques to customize the fixation to the fracture pattern. Recognition of potential dangers and use of intraoperative imaging techniques can mitigate complications. Goals of rehabilitation after the initial treatment of DRF include regaining motion, strength, and ultimately function while managing pain.